AI-Driven Governance and the Transformation of Central–Local Authority in Indonesia - Ismail Andi Muhammad Ishak; A. Ariyadi; Safaruddin Safaruddin (Government & Resilience, 2026)
Digital transformation through the use of Artificial Intelligence (AI) in governance is growing in Indonesia, triggering significant changes in the dynamics of power relations between the central and regional governments. While AI has the potential to improve the efficiency of public services and strengthen state capacity, disparities in digital capacity across regions pose significant challenges in its implementation. This study aims to analyze the impact of AI use on the configuration of authority and central-regional relations in Indonesia. The research methodology is a qualitative analysis using secondary data sources from national policy documents, local government reports, academic articles, and credible media, processed and analyzed using NVivo 12. Data were obtained from four major cities, including Jakarta, Bandung, Makassar, and Jayapura, representing varying levels of digital readiness and local challenges. The findings indicate that AI reinforces centralization and reconfigures power relations with a pattern of recentralization, through centrally controlled algorithmic standards and data interoperability. Variations in implementation indicate that local capacity and infrastructure are determinants of the success and influence of AI in local governance. This study makes a theoretical contribution by developing a framework for authority transformation in the context of digitalization in developing countries and offering empirical insights into the dynamics of central-regional relations in the AI ​​era. In addition, this study recommends strategies for increasing institutional capacity and inclusive regulatory oversight to ensure sustainable and equitable AI implementation.